Social Media Marketing Role In MSMEs - Tirta Mulyadi; Kadeni Kadeni; Susatyo Adhi Pramono; Yuliana Yuliana; Luckhy Natalia Anastasye Lotte (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
This service activity attempts to reach out to business actors who are interested in using digital marketing approaches. The service activity was attended by 25 members of the Cibiru Village Tofu business in Bandung. The implementation of activities is divided into two activity steps: socialisation and demonstration. The first step is to educate people about the importance of the internet in boosting the economy in the home industry. The second is an example of how to create a product marketing innovation using social media that can be applied immediately to all participants in the socialisation activity. As a result of this activity, participants will be able to design Kelurahanin product labels and will be able and eager to develop material for marketing strategies using social media. The realisation of success.